Mapping Pre-Service Science Teachers’ Understanding, Attitudes, and Skills in Entrepreneurial Thinking within Science Projects - Latip, Abdul; Rahmaniar, Andinisa; Zanah, Farhatul; Puspita, Diana (UNIVERSITAS NEGERI MEDAN, 2025)
This study aims to map the understanding, attitudes, and skills related to Entrepreneurial Thinking (ET) in the context of science projects among pre-service science teachers. ET is an essential component that can be integrated into science education, as it has the potential to enhance creativity, innovation, and the social impact of project-based learning outcomes. This research employed a descriptive quantitative method with a sample of 73 pre-service science teachers from various regions of Indonesia. Data were collected through an online questionnaire that measured three main aspects: conceptual understanding, attitudes, and ET-related skills within science projects. The results indicated that, in general, pre-service science teachers possess a good understanding of the concept of ET and its application in science projects. Attitudes toward ET were also highly positive, as shown by the strong enthusiasm for integrating ET into science projects. Furthermore, the participants demonstrated competency in ET-related skills, although certain aspects, such as designing innovative solutions and brainstorming, still require further development. These findings suggest that the integration of ET into science education holds significant potential in shaping innovative and solution-oriented mindsets among pre-service science teachers.